Low Carbohydrate Diet From Plant or Animal Sources and Mortality Among Myocardial Infarction Survivors. Issue 5 (22nd September 2014) - Li, Shanshan; Flint, Alan; Pai, Jennifer K.; Forman, John P.; Hu, Frank B.; Willett, Walter C.; Rexrode, Kathryn M.; Mukamal, Kenneth J.; Rimm, Eric B.
Abstract : Background: The healthiest dietary pattern for myocardial infarction (MI) survivors is not known. Specific long‐term benefits of a low‐carbohydrate diet (LCD) are unknown, whether from animal or vegetable sources. There is a need to examine the associations between post‐MI adherence to an LCD and all‐cause and cardiovascular mortality. Methods and Results: We included 2258 women from the Nurses' Health Study and 1840 men from the Health Professional Follow‐Up Study who had survived a first MI during follow‐up and provided a pre‐MI and at least 1 post‐MI food frequency questionnaire. Adherence to an LCD high in animal sources of protein and fat was associated with higher all‐cause and cardiovascular mortality (hazard ratios of 1.33 [95% CI: 1.06 to 1.65] for all‐cause mortality and 1.51 [95% CI: 1.09 to 2.07] for cardiovascular mortality comparing extreme quintiles). An increase in adherence to an animal‐based LCD prospectively assessed from the pre‐ to post‐MI period was associated with higher all‐cause mortality and cardiovascular mortality (hazard ratios of 1.30 [95% CI: 1.03 to 1.65] for all‐cause mortality and 1.53 [95% CI: 1.10 to 2.13] for cardiovascular mortality comparing extreme quintiles). An increase in adherence to a plant‐based LCD was not associated with lower all‐cause or cardiovascular mortality. Conclusions: Greater adherence to an LCD high in animal sources of fat and protein was associated with higher all‐cause and cardiovascular mortality post‐MI. We did not find a health benefit from greater adherence to an LCD overall after MI.